PENGEMBANGAN MODUL PEMBELAJARAN IPA FISIKA MATERI SUHU DAN PEMUAIAN BERBASIS POTENSI LOKAL “KERAJINAN LOGAM SAYANGAN” UNTUK SISWA SMP DI KALIBARU BANYUWANGI - Tria Yulicahyani; Trapsilo Prihandono; Albertus Djoko Lesmono (FKIP Universitas Jember, 2017)
Development of local potential “Kerajinan Logam Sayangan” based temperature and expansion of physics science learning module is a develop of module to conect between temperature and expansion of material with “Kerajinan Logam Sayangan”. The purposes of this research are to describe the validty local potential “Kerajinan Logam Sayangan” based temperature and expansion of physics science learning module, student’ learning achievement, and student’ responses. This type of research is the development, use research design 4-D. Data collection techniques used are sheets of validation, observation, interview and post-test. Local potential “Kerajinan Logam Sayangan” based temperature and expansion of physics science learning module is said good and decent to be used for teaching physics in junior high school if the product’s validity has been tested through logic validity. Result this research are: (1) logic validity real events image-based module is 4,1 with a valid category. (2) Student’ learning achievement after using local potential “Kerajinan Logam Sayangan” based temperature and expansion of physics science learning module is 63,63% with a quite good, and (3) student’ responses local potential “Kerajinan Logam Sayangan” based temperature and expansion of physics science learning module is 81,43% with a very positive. Conclusion this reseach is local potential “Kerajinan Logam Sayangan” based temperature and expansion of physics science learning module is decent to be used as a physics science of learning material in junior high school. Keyword : student’ learning achievement, student’ responses, validity